Effects of poling direction and imperfection of interfaces on a pre-stressed system with a piezoelectric core bonded to elastic faces - Daşdemir, Ahmet (SAGE Publications, 2022)
This paper models the resonance behavior of an initially stressed sandwich plate-strip consisting of a piezoelectric core and elastic faces, based on a rigid foundation, exposed to a time-harmonic force. Our research is conducted according to the linearized theory of electro-elasticity for solids under initial stress. This model assumes that there is a spring-type imperfectness at interfaces between the piezoelectric core and the face materials, both in the normal and tangential directions, and the core layer is poling in various directions. A mathematical model is created for the current problem, and then the finite element method (FEM) is used to solve it. Further, attention is focused on the influence of the mentioned imperfectness and the poling directions on the frequency response of plate-strip, in addition to the effects of the most important parameters on this response. The results show that as the imperfectness at the interface planes has the greatest effect on the horizontal polarization of the piezoelectric core, the mentioned polling direction inhibits the resonance mode of the system.